Bringing the swamp in from the periphery: Australian wetlands as sites of climate resilience and political agency. Issue 9 (28th July 2020) - Della Bosca, Hannah; Gillespie, Josephine
Abstract : Wetlands serve two increasingly critical functions in a climate-changed world, namely sequestering atmospheric carbon and moderating extremes in regional water cycles. These functions are particularly crucial in Australia, where climate change is likely to increase extreme weather events and impact water cycles. Yet despite multiscalar legal protections, Australia's total wetland cover is decreasing over time. We examine two contested wetland case studies and find that while legal mechanisms of protection exist in deliberative processes, good environmental outcomes are often undermined by the political mobility of competing commercial and industrial interests. Wetlands must be brought in from the periphery of social and political consciousness and placed at the heart of climate adaptation discourse and policy. Increasing the political mobility and agency of wetland protection has the capacity to simultaneously improve the environmental outcomes of deliberative processes and provide a legitimate pathway to greater regional climate resilience.